2012
DOI: 10.1093/humrep/der479
|View full text |Cite
|
Sign up to set email alerts
|

Antral follicle responsiveness to follicle-stimulating hormone administration assessed by the Follicular Output RaTe (FORT) may predict in vitro fertilization-embryo transfer outcome

Abstract: The observed relationship between IVF-ET outcome and the percentage of antral follicles that effectively respond to FSH administration reaching pre-ovulatory maturation suggests that FORT may be a qualitative reflector of ovarian follicular competence. Further studies with broader inclusion criteria and more personalized protocols are needed to validate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
85
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 21 publications
14
85
3
Order By: Relevance
“…23 In this study it is observed that effect of ovarian aging on FORT is negligible as compared to PFC, basal E2 and FSH levels and antral follicles continue to respond to FSH irrespective of ovarian aging which is supported by other studies. 11,24 The present study reflected that high peak E2 (at the time of OI) is associated with greater number of oocytes maturity, retrieval, fertilization, cleavage and the number of top quality embryos which enhance chances of clinical pregnancy as observed in other studies 14,25 The suggested high peak E2 for improvement of oocyte and embryo quality was observed in high FORT group of our study, similar results were shown in another study. 26,27 The increased E2 produced by growing follicles in the window of implantation, increases endometrial receptivity by apposition, attachment and apposition for the encroaching blastocyst.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…23 In this study it is observed that effect of ovarian aging on FORT is negligible as compared to PFC, basal E2 and FSH levels and antral follicles continue to respond to FSH irrespective of ovarian aging which is supported by other studies. 11,24 The present study reflected that high peak E2 (at the time of OI) is associated with greater number of oocytes maturity, retrieval, fertilization, cleavage and the number of top quality embryos which enhance chances of clinical pregnancy as observed in other studies 14,25 The suggested high peak E2 for improvement of oocyte and embryo quality was observed in high FORT group of our study, similar results were shown in another study. 26,27 The increased E2 produced by growing follicles in the window of implantation, increases endometrial receptivity by apposition, attachment and apposition for the encroaching blastocyst.…”
Section: Discussionsupporting
confidence: 90%
“…Gallot et al has established FORT as a qualitative reflector of ovarian follicle potential and quality of embryos obtained for ICSI treatment cycles as it was observed in our study that high FORT had highest number of fertilized oocytes comparable to other groups. 11,18 The present study showed that cleaved embryos were significant in high FORT group as compared to low and medium FORT groups as in another study. 38 This innovative index gives an insight to re-examine the usual criteria of abandonment of cycle just on the basis of number of growing follicles in agreement with Genro et al 18 Failure of implantation may occur in any cycle irrespective of transfer of healthy and morphologically normal embryos.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations